Advances in transport phenomena with nanoparticles and generalized thermal process for vertical plate. (16th July 2021) - Asjad, Muhammad Imran; Basit, Abdul; Iqbal, Azhar; Shah, Nehad Ali
Abstract: In this paper, a quantitative analysis is performed to investigate the convective flow of Maxwell fluid along with an erect heated plate via Prabhakar-like energy transport. The governing equations for this mathematical model are attained by Prabhakar fractional derivative. Laplace transform is applied to obtain the generalized results for dimensionless velocity and temperature profiles. By applying the conditions of nanofluid flow, we develop the constantly accelerated, variables accelerated, and non-uniform accelerated solution of the model, respectively. Prabhakar fractional derivative for Maxwell fluid based on generalized Fourier's thermal flux is determined for heat transfer. For volume fraction φ and fractional parameters α, β, and γ, different structures of graphs are obtained. Furthermore, fluid temperature and velocity can be increased by enhancing the fractional parameters' values. The comparison of nanoparticles Ag and nanoparticles Cu with water-based nanoparticles for velocity and temperature profile is also examined. The behavior of second grade and Maxwell fluid results to become a viscous fluid is justified.